Răspuns :
Răspuns:
Explicație pas cu pas:
x=[tex]\sqrt{243^{2} } -240(240+3)=\\\sqrt{243^{2} -240*243} =\\\sqrt{243(243-240} =\\\sqrt{243*3} =\sqrt{729} =27[/tex]
[tex]\sqrt{x} =\sqrt{27} =3\sqrt{3}[/tex]
a. A
b. F
c.A
d. F
Răspuns:
Explicație pas cu pas:
22)
x = √(441+2+4+6+...+880)
x = √[441+2×(1+2+3+.....+440)
x = √(441+2×440×441:2)
x = √(441+440×441)
x = √441×(1+440)
x = √(441×441)
x = √441²
x = 441
√x = √441 = 21 ∈ Z
______________________________
23) R: c)
243² - ( 240² + 3×240) =
= 243² - 240 ×(240 + 3) =
= 243² - 240 × 243 =
= 243 × ( 243 - 240) =
= 243 × 3
= 729
x = √729 = 27
√x = √27 = 3√3 ∈ R\Q